Impact of Problem‑Based Learning on Programming Skills in a Second‑Year Java Course - Moghekar, Rajeshwar; Vadla, Navakishor; Bandi, Surendra; Ch, Lokeshwar Reddy (Journal of Engineering Education Transformations, 2026)
This study investigates how Project-Based Learning (PBL) impacts programming skills in a second-year undergraduate Java course. To achieve this, we re-aligned course outcomes to emphasize core skills like debugging, collaborative problem-solving, and the application of object-oriented concepts. We replaced conventional lecture-driven instruction with a new intervention that included authentic, open-ended problem statements, structured team formation, and iterative evaluations. This approach included a dedicated debugging activity to directly measure students' ability to diagnose and correct errors. Pre- and post-surveys (5-point Likert scale) revealed notable improvements: confidence in solving programming problems increased from 3.1 to 4.2, problem-solving effectiveness improved from 3.2 to 4.3, and collaboration skills advanced from 3.3 to 4.1. In addition, classroom observations and project outcomes confirmed stronger implementation of Java features such as exception handling, multithreading, and GUI development. Challenges encountered included uneven participation within teams, integration of lateral-entry students, and occasional over-reliance on AI-assisted code generation. Overall, the study demonstrates that PBL, when explicitly aligned with course outcomes and supported by targeted debugging tasks, enhances programming competence and teamwork in the Indian undergraduate context.